THE ASSESSMENT OF CORPORATE BONDS ON THE BASIS OF THE WEIGHTED AVERAGE - Victor V. Prokhorov (Статистика и экономика, 2016)
The article considers the problem associated with the assessment of the interest rate of a public corporate bond issue. The theme of research is the study of techniques for evaluationof interest rates of corporate bond. The article discusses the task of developing a methodology for assessing the marketinterest rate of corporate bonded loan, which allows to takeinto account the systematic and speciﬁc risks. The technique of evaluation of market interest rates of corporate bonds onthe basis of weighted averages is proposed. This procedure uses in the calculation of cumulative barrier interest rate, sectoral weighted average interest rate and the interest ratedetermined on the basis of the model CAPM (Capital Asset Pricing Model). The results, which enable to speak about the possibility of applying the proposed methodology for assessing the market interest rate of a public corporate bond issuein the Russian conditions. The results may be applicable for Russian industrial enterprises, organizing issue public bonds,as well as investment companies exposed organizers of corporate securities loans and other organizations specializingin investments in the Russian public corporate bond loans.